Apolipoprotein E genotype, TNF-α 308G/A and risk for cardiac surgery associated-acute kidney injury in Caucasians. (March 2014) - Boehm, Johannes; Eichhorn, Stefan; Kornek, Matthias; Hauner, Katharina; Prinzing, Anatol; Grammer, Joachim; Lahm, Harald; Wagenpfeil, Stefan; Lange, Ruediger
Abstract Objectives: Acute kidney injury following cardiac surgery depicts a severe clinical problem that is strongly associated with adverse short- and long-term outcome. We analyzed two common genetic polymorphisms that have previously been linked to renal failure and inflammation, and have been supposed to be associated with cardiac surgery associated-acute kidney injury (CSA-AKI). Methods: A total of 1415 consecutive patients who underwent elective cardiac surgery with CPB at our institution were prospectively enrolled. Patients were genotyped for Apolipoprotein E (ApoE E2, E3, E4) (rs429358 and rs7412) and TNF-α-308 G > A (rs1800629). Results: Demographic characteristics and procedural data revealed no significant differences between genotypes. No association between ApoE (E2, E3, E4) and TNF-α-308 G > A genotypes and the RIFLE criteria could be detected. Several multiple linear regression analyses for postoperative creatinine increase revealed highly significant associations for aortic cross clamp time (p < 0.001), CPB-time (p < 0.001), norepinephrine (p < 0.001), left ventricular function (p = 0.004) and blood transfusion (p < 0.001). No associations were found for ApoE (E2, E3, E4) and TNF-α-308 G > A genotypes or baseline creatinine. When the sample size is 1415, the multiple linear regression test of R2 = 0 for seven covariates assuming normal distribution will have at least 99% power with significance level 0.05 to detect an R2 of 0.108 or 0.107 as observed in the data. Conclusions: ApoE (E2, E3, E4) polymorphism and the TNF-α-308 G > A polymorphism are not associated with renal injury after CPB.